2007
DOI: 10.1123/ijsnem.17.4.391
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effects of Glycerol-Induced Hyperhydration on Fluid Retention and Endurance Performance

Abstract: The authors determined, through a meta-analytic approach, whether glycerolinduced hyperhydration (GIH) enhances fluid retention and increases endurance performance (EP) significantly more than water-induced hyperhydration (WIH). Collectively, studies administered 23.9 ± 2.7 mL of fluid/kg body weight (BW) with 1.1 ± 0.2 g glycerol/kg BW, and hyperhydration was measured 136 ± 15 min after its onset. Compared with WIH, GIH increased fluid retention by 7.7 ± 2.8 mL/kg BW (P < 0.01; pooled effect size [PES]: 1.64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 86 publications
0
45
0
1
Order By: Relevance
“…Four studies with no exercise period examined the effect of GIH on total body water during time periods ranging from 210 to 300 min (Freund et al, 1995;Griffin et al, 1999;O'Brien et al, 2005;Riedesel et al, 1987). The average length of a typical GIH protocol is 136 min (Goulet et al, 2007). There is a trend toward an inverse relationship between the effectiveness of GCHSs in increasing fluid retention and protocol length (r = -.38, p = .09, n = 22 studies).…”
Section: Glycerol-induced Hyperhydrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies with no exercise period examined the effect of GIH on total body water during time periods ranging from 210 to 300 min (Freund et al, 1995;Griffin et al, 1999;O'Brien et al, 2005;Riedesel et al, 1987). The average length of a typical GIH protocol is 136 min (Goulet et al, 2007). There is a trend toward an inverse relationship between the effectiveness of GCHSs in increasing fluid retention and protocol length (r = -.38, p = .09, n = 22 studies).…”
Section: Glycerol-induced Hyperhydrationmentioning
confidence: 99%
“…This might be because of the lack of variation in the amount of glycerol administered by studies. Nevertheless, Goulet et al (2007) indicated that the ideal quantity of glycerol ingested to maximize fluid retention is 1-1.2 g/kg BW.…”
Section: Glycerol-induced Hyperhydrationmentioning
confidence: 99%
See 3 more Smart Citations